When Anomalies Are Publicized Broadly, Do Institutions Trade Accordingly? - Calluzzo, Paul; Moneta, Fabio; Topaloglu, Selim (Management Science, 2019)
This paper studies whether institutional investors trade on 14 well documented stock market anomalies. We show that there is an increase in anomaly-based trading when information about the anomalies is readily available through academic publications and the release of necessary accounting data. This finding is more pronounced among hedge funds and institutions with high turnover, that is, the subset of investors who likely have the abilities and incentives to act on the anomalies. We directly relate the increase in trading to the observed decay in post-publication anomaly returns. Our results support the role of institutional investors in the arbitrage process and in improving market efficiency. This paper was accepted by Renée Adams, finance.